Study of the operation of dual-mode evaporative coolers in air conditioning systems - Yarashov, Siroj; Nizomjon, Nizomjon; Hazratov, Abbos; Usmonov, Jamshid (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: most regions of Uzbekistan are covered with a hot and dry climate, and partly on the slopes of the valleys there is a hot and humid climate. Direct evaporative coolers are suitable for dry and regenerative indirect evaporative coolers for hot and humid climates. A new two-in-one evaporative cooler is proposed to avoid the use of two different coolers for the same purpose under challenging climate conditions (significant seasonal changes in temperature and humidity), and this study numerically investigates the experimental tests. The proposed cooler takes advantage of both types of evaporative coolers and operates in two modes: direct evaporative cooler for hot and dry climates and regenerative indirect evaporative cooler for hot and humid climates. The operation of both modes (direct and indirect) is explained with the help of diagrams. The effects of duct height and water flow on cooling capacity, wet bulb efficiency, and dew point efficiency are discussed. Aim: the aim of this research work is to introduce a new dual-mode heat and mass exchanger, which is a two-in-one device operating in direct and indirect modes for hot-dry and hot-humid weather conditions, respectively. Methods: differential discretization derived from the conservation of mass and energy in the channels was used using the finite difference method. Results: the performance of the proposed cooler was assessed for five cities of Uzbekistan (Karshi and Termez with a hot arid climate, Andijan, Namangan and Fergana with a hot humid climate). During the warm months (April to October) and in cities, the suitability of the regimes is assessed using a psychometric table. The research results show that the proposed cooler can be effective and economical to use for regions with mixed climates.